The Australian money market - WILSON, J.S.G. (PSL Quarterly Review, 2013)
This article considers first the early history of the Australian money market. A serious market first began to emerge in the 1950s, catalysed by stock and share brokers. However it was not until 1959 that lender-of-last-resort facilities became available to ensure market liquidity for official market makers. Over recent years the greatest growth has been in the unofficial sectors. The article reviews the role and nature of participants and the instruments traded and asks whether the demise of the official market makers is imminent. JEL: F30